Thermal bridges in a prefabricated wooden house: comparison between evaluation methods. Issue 5 (19th October 2016) - Troppová, E.; Klepárník, J.; Tippner, J.
ABSTRACT: The major aim of this study was to create a numerical model of thermal bridges in a wooden structure and to discover differences between factual values of linear thermal transmittance utilized in the finite-element (FE) modelling and values given by the European normative method (EN ISO 14683). Thermal bridges of wooden structures were detected using thermocamera FLIR S65 for infrared detection. These measurements allow displaying the temperature distribution of the thermal scan and proving the positive correlation between heat flux and change in the evaluated temperatures of a thermal bridge. A three-dimensional FE model of the structure was prepared for the thermal analysis using the engineering software ANSYS Workbench 13. The transmission heat loss coefficients of a prefabricated wooden house were established based on the Czech normative method (ČSN 730540-4). Linear thermal transmittance values calculated from the thermal analysis and the normative method given by EN ISO 10211 were compared. The results show that even if the transmission heat loss coefficients meet the requirements designated by standards, the real heat losses are increased by thermal bridges involved in the construction. Their influence is determined by the linear transmittance value which is usually not exactly established.